Application of residue, inorganic fertilizer and lime affect phosphorus solubilizing microorganisms and microbial biomass under different tillage and cropping systems in a Ferralsol - Bolo, Peter Omondi; Kihara, Job Maguta; Mucheru-Muna, Monicah; Njeru, Ezekiel Mugendi; Kinyua, Michael; Sommer, Rolf (Elsevier, 2021)
Phosphorus is a critical nutrient for plant growth. Several agronomic practices have been promoted to improve soil fertility and crop productivity in Western Kenya. Yet, despite their benefits, a dearth of knowledge exists on their long-term effects on soil microbial biomass and phosphorus solubilizing microbial species (PSMs) abundance especially in this region. In a long-term (15 years) agronomic field trial, we selected 8 treatments that allowed for evaluation of 1) Effect of tillage in a maize-soybean rotation with fertilization and residue retention; 2) Effect of residue retention in a maize-soybean rotation with fertilization under conservation tillage; 3) Effect of N and P fertilization in a maize-soybean rotation with conventional tillage; 4) Effect of liming in a maize-soybean intercropping with conventional tillage; and 5) Effect of maize-soybean rotation versus intercropping under conservation tillage on microbial biomass and PSMs abundance. The study was conducted in a long-term conservation agriculture experiment (30 seasons) in a Ferralsol in Western Kenya in 2016 and 2017. Reduced tillage significantly (P < 0.05) increased microbial biomass phosphorus (MBP) and abundance of different PSMs relative to conventional tillage, though the results were not consistent for some species. Residue addition significantly increased MBP and abundance of different PSMs compared to systems without residue addition. Liming significantly reduced PSMs abundance in 2016, though this was inconsistent for 2017. In 2017, no effect of liming on soil pH was found. Fertiliser addition significantly increased PSMs abundance in 2016, but this was also inconsistent for 2017. Some PSMs strains were significantly more abundant in maize and soybean intercropping system compared to rotation, and vice versa. Our study demonstrated that not only the agronomic inputs applied but also tillage and cropping systems employed can variably affect the soil microbial populations.